How does learning keep a small company afloat? - Hundermark, Genevieve (Information Management and Business Review, 2014)
Small and medium enterprises in South Africa experience one of the highest failure rates in the world with approximately 90% failing in their first ten years, suggesting that few are sustainable entities. In order to be sustainable, organisations should be learning ones. Senge’s (1990) ground-breaking model of a learning organisation, previously researched in large global companies, was used as the basis of researching a small company in South Africa. The study explored whether by being a learning organisation, the company could sustain itself. Senge’s model includes five disciplines, with embedded adult learning theories. An ethnographic case study attempted to identify whether the company drew on these learning theories in its operations, and if this contributed to its development as a learning organisation. The study revealed an interesting blend of a business management concept with adult education principles that gave insight into developing the small company as a learning organisation.